2002
DOI: 10.1212/wnl.59.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of cerebral blood flow reduction in patients with ischemic leukoaraiosis

Abstract: Hypoperfusion may be an early feature in the development of periventricular lesions in ILA and may play a direct pathogenic role. Serial studies are now needed to determine whether these changes herald the appearance of new lesions and represent "at risk" white matter, and to determine whether pharmacological agents can restore perfusion of normal-appearing white matter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
243
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(262 citation statements)
references
References 20 publications
16
243
1
2
Order By: Relevance
“…An alternate explanation for poor outcomes in patients with leukoaraiosis may be chronic cerebral hypoperfusion that results in reduced cerebral ischemic resilience and thus greater final lesion volumes, 20 which are a known outcome predictor after EST. 21 Indeed, we and others have previously shown that leukoaraiosis severity is associated with a larger ischemic core, mismatch lost, and final infarct volume, supporting this hypothesis.…”
Section: Multivariable Logistic Regression Analysis Of Factors Indepementioning
confidence: 99%
“…An alternate explanation for poor outcomes in patients with leukoaraiosis may be chronic cerebral hypoperfusion that results in reduced cerebral ischemic resilience and thus greater final lesion volumes, 20 which are a known outcome predictor after EST. 21 Indeed, we and others have previously shown that leukoaraiosis severity is associated with a larger ischemic core, mismatch lost, and final infarct volume, supporting this hypothesis.…”
Section: Multivariable Logistic Regression Analysis Of Factors Indepementioning
confidence: 99%
“…The tortuosity of some of these arterioles leads to losses in hemodynamic kinetic energy [14]. Studies with MRI [15] and PET [16,17] have found decreased blood flow in the white matter of subjects with LA, and the blood flow was even reduced in normal-appearing white matter [15]. Thus, the vascular pathology and blood flow changes suggest that LA results from chronic ischemia [5,8,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…CKD is a salt-avid state, and the salt overload aggravates both HTN and systemic inflammation autoregulation with subsequent transmittal of increased systemic pressure into the glomerulus and cerebral capillary beds. Loss of autoregulation also predisposes to ischemic events related to decrease of regional cerebral blood flow (CBF) [19,20]. Hypertension worsens arteriolosclerosis, creating a vicious cycle that perpetuates end organ damage.…”
Section: Accelerated Arteriolosclerosis With Impaired Autoregulationmentioning
confidence: 99%